Infectious Diseases and Socio-Demographic Determinants of Stunting among Children Aged 6-24 Months: A Multivariable Analysis - Sumarah Sumarah; Dyah Noviawati Setya Arum; Sri Endang Windiarti; Rita Rena Pudyastuti (Jurnal Promosi Kesehatan Indonesia, 2026)
Background: Stunting is a nutritional health issue in Indonesia. It results in growth and developmental disorders among children under five years. Numerous variables can contribute to stunting. This study aimed to determine the influence of a history of infectious diseases on stunting among children aged 6 to 24 months in the Turi Health Center working area, Sleman Regency, Special Region of Yogyakarta.Method: This study employed a case-control design using purposive sampling. The study population consisted of children aged 6-24 months at Turi Primary Health Center, Sleman, Indonesia. A total of 100 respondents were assigned to the case and control groups. Participants were selected from medical records based on inclusion criteria. Data were collected through interviews with parents and medical record review. Anthropometric measurements were obtained from growth monitoring records and measured or confirmed by trained health workers using standardized length boards and calibrated scales. Data analysis used univariable, bivariable (Chi-square and OR), and multivariable logistic regression.Result: The incidence of stunting was significantly associated with a history of infectious diseases and respiratory tract infections, with p-values of 0.000 for both variables. Multivariable analysis showed that Respiratory tract infection was the most dominant factor associated with stunting, with an OR of 5.370 (95% CI: 1.572-18.340; p = 0.007). Mother’s education was also significantly associated with stunting, with an OR of 2.593 (95% CI: 1.208-5.565; p = 0.014). Children’s age showed a borderline association with stunting, with an OR of 0.387 (95% CI: 0.150-0.999; p = 0.050). Keywords: History of infection diseases, Stunting, Children aged 6-24 months